Teknologi pembuatan pupuk organik cair (POC) berbahan dasar air cucian beras pada tanaman sayuran organik di pekarangan: Technology for making liquid organic fertilizer (LOF) based on washed rice water for organic vegetable plants cultivation in the yard - Andi Nurmas; Robiatul Adawiyah; Makmur Jaya Arma; Norma Arif; Sarawa Sarawa; Dirvamena Boer (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
The problems of members of the Manggarai Women’s Farmers Group in Padaleu Village, Kambu District, Kendari City are (1) so far no party has socialized the adverse effects of using inorganic fertilizers and the trend of public awareness of consuming organic food ingredients so that farmers are directed to use organic fertilizers. (2) the target audience has not received an explanation about LOF, including the basic ingredients, benefits, how to make it, and its application to vegetable plants in the yard. This activity aims to (1) Improve the knowledge of Women Farmer Group members about the adverse effects of using inorganic fertilizers, (2) Provide understanding to the community about using rice washing water as a basic ingredient for LOF, and (3) Increase knowledge about LOF methods, materials and applications. This activity begins with direct observation in the field to discover the problem and determine the method used in the activity—next, socialization with members of the Women’s Farmers Group. The method used is a combination of counseling and technical guidance as follows: (1) Socialization through delivering materials, lectures and discussions regarding the negative impacts of inorganic fertilizers used on humans, soil and the environment; the importance/benefits of LOF and what basic ingredients can be used in making LOF; and benefits of LOF, and (2) Making liquid organic fertilizer based on rice washing water with the help of EM-4 to be applied to organic vegetable plants in the yard. LOF is fermented for 2 weeks, resulting in a 60 L volume. Applying LOF based on rice washing water can increase the growth and yield of vegetable plants in the yard.